2020
DOI: 10.3390/ijerph17197326
|View full text |Cite
|
Sign up to set email alerts
|

The Mortality Risk and Socioeconomic Vulnerability Associated with High and Low Temperature in Hong Kong

Abstract: (1) Background: The adverse health effect associated with extreme temperature has been extensively reported in the current literature. Some also found that temperature effect may vary among the population with different socioeconomic status (SES), but found inconsistent results. Previous studies on the socioeconomic vulnerability of temperature effect were mainly achieved by multi-city or country analysis, but the large heterogeneity between cities may introduce additional bias to the estimation. The linkage b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Lu et al indicated that the burden of cardiovascular hospitalizations caused by high temperature could increase in the context of global warming 36 . Consistent with this study, many studies indicated that while the burden of temperature-related mortality may shift to higher temperature in the future, cold temperature may be a bigger problem in temperate cities today 27 , 37 , 38 . A review reported that deaths and hospitalizations due to extreme heat increased sharply in the Detroit area, while deaths due to cold temperatures increased gradually 27 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Lu et al indicated that the burden of cardiovascular hospitalizations caused by high temperature could increase in the context of global warming 36 . Consistent with this study, many studies indicated that while the burden of temperature-related mortality may shift to higher temperature in the future, cold temperature may be a bigger problem in temperate cities today 27 , 37 , 38 . A review reported that deaths and hospitalizations due to extreme heat increased sharply in the Detroit area, while deaths due to cold temperatures increased gradually 27 .…”
Section: Discussionsupporting
confidence: 87%
“…A review reported that deaths and hospitalizations due to extreme heat increased sharply in the Detroit area, while deaths due to cold temperatures increased gradually 27 . A study conducted in Hong Kong noted that low temperatures had a greater impact on non-accidental, cardiovascular, respiratory, and cancer deaths than high temperatures 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from all-cause or non-external causes of mortality, cardiovascular and respiratory deaths have been found to be associated with both heat and cold exposure [ 4 , 9 , 10 , 11 , 12 ], with V-, U-, or J-shaped temperature–mortality relationships observed, with the optimum temperature corresponding to the lowest point in the curve. Other causes, including cancer, have been shown to have a substantially weaker association with ambient temperatures [ 6 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other causes, including cancer, have been shown to have a substantially weaker association with ambient temperatures [6,13].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, five studies are published to delineate population health risks that may be associated with climate change in various contexts. The studies examine socio-demographic patterns of self-help and community bottom-up health protection strategies during extreme temperature events [ 7 , 8 ] (Lam et al, Liu et al) and typhoon/hurricane [ 9 , 10 ] (Shang et al, Shih et al). In addition, with the global increasing health risks associated with vector-borne diseases as a result of climate abnormalities, [ 11 ] Chan et al present a narrative review paper of the current understanding of primary preventive Health-EDRM measures that might reduce the health risks of vector-borne disease in communities.…”
mentioning
confidence: 99%